HUBUNGAN KOMPONEN FLEXIBILITY TERHADAP AKURASI SERVIS PADA PERMAINAN SEPAK TAKRAW DI PSTI BOJONEGORO - Ramadhan, M. Fachrizal Wahyu (Journal of Sport and Exercise Science, 2021)
In the game of sepak takraw, serve is very important because it can be the first attack. To produce a good service, there are supporting factors, one of which is the flexibility ability of a tekong. This study aims to determine the relationship between flexibility components and service accuracy in the sepak takraw game at PSTI Bojonegoro. This study uses two variables, namely the independent variable and the dependent variable. This type of research is quantitative with a correlational research design. The population in this study were all 5 tekong athletes at PSTI Bojonegoro. The test instruments in this study were sit and reach tests and service accuracy tests. The data analysis technique used simple correlation (bivariate correlation). The results of the statistical data analysis of the Pearson bivariate correlation, it is known that there is a significant relationship between flexibility and service accuracy with a significance value (p <0.05) and the Pearson correlation value (p = 0.987) which is included in the very strong Pearson correlation interpretation. From these results, it can be concluded that there is a significant relationship between flexibility and service accuracy at PSTI Bojonegoro.